1994
DOI: 10.1103/physrevb.49.16474
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-resolved spatial variations in the Schottky barrier height of a Au/n-type GaAs diode

Abstract: Nanometer-resolved lateral variations in the Schottky barrier height (SBH) formed at a chemically prepared Au/n-type GaAs interface were measured using ballistic-electron-emission microscopy (BEEM). The spatial profile and the statistical distribution of the SBH's thus obtained were compared to current-voltage (IV) and capacitance-voltage {CV) characteristics of the same metal-semiconductor contact. This comparison showed that the macroscopic SBH obtained from the IV measurements can be successfully interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 12 publications
3
25
1
2
Order By: Relevance
“…Each error bar is the result of 20 to 30 local measurements. The size of the error bar ranges from 30 to 50 meV, which is comparable with the local variation of Au/GaAs Schottky barrier height obtained by Williams et al 21 Tip drift limited our spectroscopy resolution to about 5-10 nm, which is an order of magnitude higher than the theoretical limit. This may have resulted in less measured variation since BEEM spectroscopy was averaged over a larger area.…”
supporting
confidence: 55%
“…Each error bar is the result of 20 to 30 local measurements. The size of the error bar ranges from 30 to 50 meV, which is comparable with the local variation of Au/GaAs Schottky barrier height obtained by Williams et al 21 Tip drift limited our spectroscopy resolution to about 5-10 nm, which is an order of magnitude higher than the theoretical limit. This may have resulted in less measured variation since BEEM spectroscopy was averaged over a larger area.…”
supporting
confidence: 55%
“…Recently, ballistic electron emission microscopy ͑BEEM͒ techniques demonstrated that nanoscale inhomogeneities give rise to nonideal macroscopic behavior in the I -V characteristics of a diode. [3][4][5][6][7] The scanning tunneling microscope in these experiments, however, allows only very small contact areas to be probed. In this letter, we investigate transport through the Schottky barrier of PtSi/Si contacts by examining the lowtemperature current versus gate voltage (I -V g ) characteristics in Schottky-barrier metal-oxide-semiconductor fieldeffect transistors ͑SBMOSETs͒.…”
mentioning
confidence: 99%
“…It is confirmed by direct studies of the distribution of the barrier height in contacts with ballistic electron emission microscopy (a BEEM-method). 16 However, studies [17][18][19][20][21][22][23][24] (and others) evidently do not indicate that the "saddle points" play the main role in the observed "anomalies" in the contact characteristics, but do not exclude other factors playing a similar role. It should also be noted that for comparison with experiment, a highly simplified version of the model of "saddle points" with the IVC significantly different from the exact expression 25 (Eq.…”
mentioning
confidence: 86%